Management of Cerebellar Tonsillar Herniation following Lumbar Puncture in Idiopathic Intracranial Hypertension - Kenneth R. Hoffman; Sean W. Chan; Andrew R. Hughes; Stephen J. Halcrow (Case Reports in Critical Care)
Lumbar puncture is performed routinely for diagnostic and therapeutic purposes in idiopathic intracranial hypertension, despite lumbar puncture being classically contraindicated in the setting of raised intracranial pressure. We report the case of a 30-year-old female with known idiopathic intracranial hypertension who had cerebellar tonsillar herniation following therapeutic lumbar puncture. Management followed guidelines regarding treatment of traumatic intracranial hypertension, including rescue decompressive craniectomy. We hypothesize that the changes in brain compliance that are thought to occur in the setting of idiopathic intracranial hypertension are protective against further neuronal injury due to axonal stretch following decompressive craniectomy.